Widely Tunable C +L Bands Multiwavelength BEFL with Double-Brillouin Frequency Shifts - Almusafer W.K.H.; Jamaludin M.Z.; Abdullah F.; Al-Mansoori M.H.; Ajiya M.; Mahdi M.A. (2023)
A wideband multiwavelength Brillouin-erbium fiber laser (BEFL) with double Brillouin frequency spacing is demonstrated. The fiber laser structure utilizes a tunable band-pass filter and a pre-amplified Brillouin pump technique within a ring cavity. An average of six Brillouin-Stokes signals in C + L bands with a constant wavelength spacing of 0.174 nm can be turned over a span of 80 nm from 1530 nm to 1610 nm. Total average output power of 8.5 mW from this laser structure was achieved. All the generated Brillouin-Stokes signals exhibit good stability, and high peak power of above -10 dBm per signal was demonstrated. 2012 IEEE